Pengaruh Dokter Detektif (Doktif) Dalam Bisnis Skincare : Antara Kepercayaan Konsumen Dan Kepatuhan Hukum - Diandra Azzahra Isabella; Fazara Aspasari; M. Abdilah Maghfiro (Jurnal Riset Multidisiplin Edukasi, 2025)
Influencers on social media have a significant impact on public perception, especially when it comes to skincare and beauty product education. The foundation of this study is user protection against the use of overly dramatic claims (overclaims) in skincare advertising that may be harmful to consumers, such as exaggerated claims for skincare ingredients. This research aims to explore the role of influencers in educating the audience on the TikTok account "DokterDetective" which often discusses skin care products with excessive claims and legal protection issues related to these claims in skin care marketing. Apart from that, this research also examines the responsibility of producers who still use sentences that contain excessive claims. The research results show that the information conveyed by manufacturers regarding skincare products with excessive claims has the potential to harm consumers and does not meet the criteria for information that should be conveyed in sales. The use of excessive claims is very contrary to applicable law, including the obligations of producers and consumer rights, as well as the provisions in Article 3 paragraph (2) of the 2022 BPOM Regulations and Article 3 of BPOM Regulations Number 32 of 2021. Producers who use overclaims are seen to cause material losses in the form of funds spent and immaterial losses in the form of physical losses and disappointment, in this case the producer must be responsible for these losses. Responsibility of producer is explained in articles 19-20 UUPK, articles 1365-1367, KUHP, and BPOM regulation number 3 of 2022.